Northern Star : Canada's Path to Economic Prosperity - Klyuev, Vladimir; Bayoumi, Tamim; Muhleisen, Martin (Washington, D.C. : International Monetary Fund, 2007)
Robust GDP growth, declining unemployment, low and stable inflation, and a string of fiscal and current account surpluses -- it's a record to be envied. These outcomes in Canada owe much to sound macroeconomic policies, as well as to a favorable external environment. This book focuses on these policies and the economy's salient features, including its close trade integration with the United States, large commodity sector, and substantial decentralization and regional diversity. It outlines what is unique about the Canadian experience and sheds light on policies and philosophies that can be fruitfully applied in other economies.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet